Proposal of Fully Integrated LED Driver with Enhanced Power Density for Street-lighting Applications - Barboza, Igor B. (2025)
This paper proposes a new fully integrated Boost and Buck converter. The topology results from integrating the Boost as the power factor correction (PFC) stage and the Buck as power control (PC) stage. Besides this, the paper presents a methodology for designing the PFC stage inductor based on the inductance ratio between the PFC and PC stage inductances. In this work, the methodology analysis is carried out to enhance the converter power density using magnetics integration. Magnetic circuits and finite elements simulations compare the standalone and the integrated magnetics designs. Finally, the methodology is validated for the proposed fully integrated topology by implementing an 180~W LED driver prototype, which works properly for the grid voltage range (180-250~$V_{rms}$) and ensures full DCM operation between 10 and 100% of the LED load power. The experimental results show that the proposed topology fulfills the recommendation IEEE 1789-2015 and the standard IEC 61000-3-2 (Class C) in the grid range. The peak efficiency is 93.5% at 180~$V_{rms}$. The integrated magnetic enables a volume reduction of 20% compared to the standalone magnetics. The converter component count is significantly reduced compared to LED drivers found in the literature for street-lighting applications.